“Mothering the Politics”: Care, Affect, and the Digital Construction of Maternal Leadership in Local Government - Rony Agustino Siahaan (Universitas Multimedia Nusantara, 2026)
This study examines how maternal identity operates as a communicative practice of governance within digitally mediated political environments. Focusing on the case of Sherly Tjoanda, Governor of North Maluku, Indonesia, the research analyzes how maternal leadership is constructed through the interaction between official social media performances and public reinterpretations circulating through YouTube Shorts. Using digital ethnography, the study examines three interconnected datasets: official Instagram posts documenting governing activities, publicly produced YouTube Shorts that remix and circulate these performances, and audience comments that express emotional and moral evaluations. The analysis identifies four communicative dynamics through which maternal leadership becomes recognizable and legitimate: performative identity, communicative constitution through circulation and recognition, affective engagement within digital publics, and care-based ethical framing. The findings show that motherhood functions not merely as symbolic political branding but as a relational infrastructure through which governance is narrated, interpreted, and legitimated. Short-form videos amplify gestures of care, emotional interactions, and narratives of protection, allowing networked publics to participate in the communicative constitution of maternal leadership